2019
DOI: 10.3390/insects10070214
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exclusion Netting Row Covers on ‘Honeycrisp’ Apple Trees Grown under Northeastern North American Conditions: Effects on Photosynthesis and Fruit Quality

Abstract: Exclusion nets have been used successfully to protect fruit from insect pests of apples under various conditions, but the effect of each particular netting system on the plant itself has rarely been investigated. In this study, a complete exclusion system—in which the soil is also excluded—was used to grow ‘Honeycrisp’ apples for six years in southern Quebec, Canada. Abiotic conditions, as well as plant photosynthesis and fruit quality characteristics (colour, firmness, size, sugar content, number of seeds, ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…The percentage of red color under black hail net was significantly reduced compared to a control [53]. Chouinard et al, showed reduced fruit color of 'Honeycrisp' in netted trees compared to non-netted trees in several years of a six-year netting study, though annual variation in fruit quality attributes was considerably high [38]. For 'Honeycrisp', trees netted at 'pink' had~15-30% fewer fruit than their later-netted counterparts in both years, albeit non-significantly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of red color under black hail net was significantly reduced compared to a control [53]. Chouinard et al, showed reduced fruit color of 'Honeycrisp' in netted trees compared to non-netted trees in several years of a six-year netting study, though annual variation in fruit quality attributes was considerably high [38]. For 'Honeycrisp', trees netted at 'pink' had~15-30% fewer fruit than their later-netted counterparts in both years, albeit non-significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, tree response to exclusion netting varied considerably based on biological (e.g., genotype) and environmental factors. For example, alteration of fruit quality under exclusion netting differed among seasons as a function of the environmental conditions [38,39]. Further, nets vary considerably in material construction (type of polymer, density, color, weave, etc.…”
Section: Global Organic Fruit Production Increased 109% Between 2008 mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, exclusion nets modify the plant’s growing environment and can have a number of positive effects on the physiology of the plant (e.g., reducing water stress by lowering evaporative demand, reducing heat stress by shading, and reducing light stress by improving the penetration of spectrally modified light into the canopy) [ 49 , 50 , 51 , 52 ]. This reduction in environmental stressors often translates to improved photosynthesis and vegetative development, increased fruit set, larger fruit size, changes in time to maturation (either advancing or delaying harvest), and improved fruit quality [ 53 , 54 ]. Crops for which exclusion systems are best suited are those that are high value, perennial, and grown over a logistically manageable space for net installation.…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion netting systems appear to represent a good alternative to insecticides and may become the norm for organic orchard management in the future (Chouinard et al, 2017(Chouinard et al, , 2019. Currently, nets must be opened for a few hours on 2-3 suitable days during bloom to ensure successful pollination by honey bees and adequate fruit set.…”
Section: Introductionmentioning
confidence: 99%